Prevention of urinary stone diseases - Madaminov Muhammedvali Ikromjon O’g’li (Zien Journals, 2022)
This article provides information about kidney stone disease and its prevention and treatment
Keywords: Kidney stone disease; urinary tract; urinary stone disease; urologist